2014
DOI: 10.1007/s11434-014-0635-5
|View full text |Cite
|
Sign up to set email alerts
|

Compression behavior of Sm2Ti2O7-pyrochlore up to 50 GPa: single-crystal X-ray diffraction and density functional theory calculations

Abstract: Single-crystal X-ray diffraction at pressures up to 50 GPa has been employed to study the compression behavior of Sm 2 Ti 2 O 7 -pyrochlore. In contrast to earlier reports, we observed no pressure-induced amorphization or pressure-induced anion disorder up to 50 GPa. The experimental study has been complemented by density functional theory-based calculations. A combination of the theoretical and experimental data yields a bulk modulus of %185 GPa, significantly higher than a value which had been reported earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The cationic radii are from Shannon, 1976 [25]. # is from the single crystal high-pressure XRD [26]. * is from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The cationic radii are from Shannon, 1976 [25]. # is from the single crystal high-pressure XRD [26]. * is from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed comparison between our results and DFT predictions [40][41][42][43][44] as well as available experimental data [45][46][47][48] is listed in Table 2. It can be seen that our calculated results are generally in good agreement with experimental measurements (noted Exp.…”
Section: Bulk Modulusmentioning
confidence: 93%
“…This was followed by one more high-pressure XRD study on Tb 2 Ti 2 O 7 that reported structural transition to monoclinic phase at 39 GPa . High-pressure Raman and XRD investigation of Sm 2 Ti 2 O 7 shows anionic disorder around 40 GPa, but recent high-pressure single-crystal study and density functional theory calculations did not support this finding of Sm 2 Ti 2 O 7 . Similarly Raman and XRD studies on Yb 2 Ti 2 O 7 have revealed a reversible structural transition to monoclinic phase at 28.6 GPa .…”
Section: Introductionmentioning
confidence: 92%
“…12 High-pressure Raman and XRD investigation of Sm 2 Ti 2 O 7 shows anionic disorder around 40 GPa, 8 but recent high-pressure single-crystal study and density functional theory calculations did not support this finding of Sm 2 Ti 2 O 7 . 13 Similarly Raman and XRD studies on Yb 2 Ti 2 O 7 have revealed a reversible structural transition to monoclinic phase at 28.6 GPa. 10 XRD studies at high pressures on Ho 2 Ti 2 O 7 and Y 2 Ti 2 O 7 have indicated structural transition to monoclinic phase at 37 and 42 GPa, respectively.…”
Section: ■ Introductionmentioning
confidence: 98%